Keanekaragaman dan Sebaran Nepenthes di Hutan Pendidikan Hampangen Universitas Palangka Raya, Kalimantan Tengah - Muhammad Hanafi (Journal of Biotropical Research and Nature Technology, 2025)
This study aims to identify Nepenthes species' diversity and distribution to analyze spatial dispersion patterns in Hampangen Educational Forest, University of Palangka Raya. The study used an explorative method using purposive sampling techniques in three observation sites. Environmental parameters such as air temperature, humidity, and soil pH were measured to analyze habitat conditions. The results indicate the presence of four Nepenthes species: Nepenthes gracilis, Nepenthes rafflesiana, Nepenthes ampullaria, and Nepenthes mirabilis. The distribution of these species varies across different observation sites, with N. ampullaria being the specifically distributed species. Habitat characteristics show that these Nepenthes thrive in secondary peat swamp forests. This research provides baseline data for conservation efforts and further ecological studies.